MicroRNA-16, via FGF2 Regulation of the ERK/MAPK Pathway, Is Involved in the Magnesium-Promoted Osteogenic Differentiation of Mesenchymal Stem Cells. (27th April 2020) - Qi, Hong; Liu, Yang; Wu, Lu; Ni, Su; Sun, Jing; Xue, Junchao; Liu, Qizhan; Ni, Xinye; Fan, Weimin
Abstract : microRNAs (miRNAs) participate in the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). However, few reports have discussed the effect of miRNAs on the magnesium chloride (MgCl2 )-induced promotion of osteogenic differentiation of BMSCs, a process involved in the healing of bone tissue. As determined in the present investigation, MgCl2 decreased miR-16 levels; increased levels of fibroblast growth factor 2 (FGF2), p-p38, and p-ERK; and promoted the osteogenic differentiation of BMSCs. Enhancement of miR-16 levels by an miR-16 mimic blocked these MgCl2 -induced changes. Moreover, luciferase reporter assays confirmed that miR-16 binds to the 3 ′ UTR region of FGF2 mRNA. Down-regulation of FGF2 blocked the MgCl2 -induced increases of p-p38 and p-ERK and the promotion of the osteogenic differentiation of BMSCs. Furthermore, over-expression of miR-16 attenuated the MgCl2 -induced overproduction of p-p38 and p-ERK1/2 and the high levels of osteogenic differentiation, effects that were reversed by elevated expression of FGF2. In summary, the present findings provide a mechanism by which miR-16 regulates MgCl2 -induced promotion of osteogenic differentiation by targeting FGF2-mediated activation of the ERK/MAPK pathway.